Adventures in English syntax - Freidin, Robert (Cambridge University Press, 2019)
"An understanding of English sentence structure is a powerful, practical, and indispensable tool for anyone who wants to become a more effective writer, a more perceptive reader, and a more precise thinker. This book shows you how to begin. Using clear and engaging examples from English, it introduces the basic concepts of syntactic structure to readers with no background in linguistics. Starting with simple, familiar phrases, and progressing to more complex sentences, it builds on what we already intuitively know, to provide a step-by-step account of why we understand these examples as we do. It then shows how that understanding can be applied to writing, helping us to avoid some of the common hallmarks of 'bad writing', such as ambiguity, redundancy, and vagueness. A unique and valuable resource, this book will enrich users' understanding of English in ways that will make them more effective writers, and readers, of the language.